(untitled) (Global Journal of Human-Social Science, 2023)
Objectives The main aim of this study is to identify the existing relationships between various inside and interpersonal factors and personality traits concerning to dysfunctional jealous behavior with individuals involved in romantic relationships Material and Methods Quantitative questionnaires inventories and scales and experimental data have been used to measure and test the study s hypothesis A sample of 180 participants has been measured on personality traits dysfunctional attitudes and level of resilience in front of family stressful events Results The findings show that jealousy as a feature of attachment trauma significantly correlates p 0 001 with several personality factors such as neuroticism r 0 57 dependency r 0 49 psychoticism r 0 45 culpability r 0 57 and ergic tension r 0 60 Contrary to previous research the results indicate no significant effect F 1 69 p 0 172 of life events and stressful family life on the experience of jealousy in the later years Conclusions Personality traits start developing within early childhood influenced mainly by the family environment a child is brought in But as time goes by individuals can become more attached to the new relationships they get involved in displaying attitudes and behaviors guided mainly by their innermost fears and insecurities reflected in jealous behavior Romanian individuals appear to discount the family background and hardships they come from manifesting more loyalty to their family of origin as seen in the findings of the quantitative data